PREVALENCE OF DEPRESSION IN A SAMPLE OF IRAQI PATIENTS WITH RHEUMATOID ARTHRITIS (World Bulletin of Public Health, 2022)
Rheumatoid arthritis (RA) is a common chronic systemic autoimmune inflammatory disease that affects all ethnic groups throughout the world. It leads to chronic articular, extra-articular manifestations and disability. Depression is a common sequel of RA and it is a mental illness characterized by a profound and persistent feeling of sadness or despair and\or loss of interest. Depression is important contributor to poor health outcome in RA patients
Keywords: Rheumatoid arthritis; Depression